The influence of Jigsaw-based Cooperative learning model on students’ critical thinking skills of light wave concepts - Sugiyanto, Lina Alysa; Andriani, Dini; Adimayuda, Rizal (Insitut Pendidikan Indonesia, 2025)
This study aims to examine the influence of the Jigsaw-based cooperative learning model on students’ critical thinking skills in the concept of light waves. The background of this study is based on the low levels of students’ active participation and the underdeveloped critical thinking skills in physics learning, which have been traditionally dominated by conventional approaches. The Jigsaw model was chosen because it can promote active student engagement in group learning, enhance scientific communication, and foster a deeper conceptual understanding. This study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The research sample consisted of 20 students from Grade XI-1 at one public school in Indonesia. The instrument used was a written test of critical thinking skills based on Ennis’s indicators. Data analysis using the paired sample t-test revealed a significant difference between pretest and posttest scores, with a significance value of 0.000 < 0.05. Additionally, the N-Gain calculation showed an average improvement categorized as medium (0.35). Therefore, it can be concluded that the Jigsaw-type cooperative learning model has a positive effect on enhancing students’ critical thinking skills in the topic of light waves.